IMPLEMENTASI MANAJEMEN KEPALA SEKOLAH DALAM MEWUJUDKAN BUDAYA RELIGIUS - Nur Aini; Sulthan Syahril; Dewi Yanti (UNISAN JURNAL, 2023)
Islamic educational institutions are not complete when the knowledge about religion of educators (teachers) and employees is still minimal. Religious culture in an educational institution really needs to be emphasized, even if it is an Islamic-based educational institution. Because religious culture is a set of religious values ​​that underlies behavior, traditions, habits, and symbols that are practiced by teachers as educators in Islamic schools. Religious culture is a way of thinking and acting of school members based on religious values ​​(diversity). Qualitative research approach with a descriptive approach type. Data collection techniques used in this study are: observation, interviews, and documentation. The results of the study show that the religious culture that is developed is: sunnah dhuha prayer, recitation of rotibul haddad (dhikr), Tadarus Al-Qur'an, friendly attitude (smiles, greetings, and greetings). The principal's management strategy in building a religious culture is: Mutual communication, habituation, Commemoration of Islamic holidays, Furudul 'ainiyah